Factors influencing cloud computing adoption in government agency / Zurina Jusoh - Jusoh, Zurina (2014)
Cloud Computing is the latest trending of information technology. Cloud Computing is a computer technology that allowing a user to share information and an organization can have a benefit of powerful computer infrastructure to reduce cost to pay capital cost like hardware and software. The employees in organization can access the data from everywhere, information and application on Cloud Computing through internet. The objectives of this study are to identify what type services of cloud that have been used by the government agency. This study will also highlight (or examine) on the factors influencing in adopting Cloud Computing from environmental and organizational factors, complexity factors, compatibility factors, security and privacy factors, trial ability and cost factors in government agency to see all the factors can adopt in government agency. This study use questionnaires to find the factors that adopt Cloud Computing in government agency. For analysis this study makes content analysis descriptive, frequencies, and Pearson correlation coefficient for validity techniques. This study is using quantitative and qualitative methodology. The finding of type of cloud service is Software as a Service (SaaS) and factors influencing for Cloud Computing adoption in government agency are trial ability and cost factors. This findings hope can give information the Cloud Computing adoption in an organization.